Aspek yang mempengaruhi keputusan pembelian dan kepuasan pelanggan pada Rumah Makan Hasrat - Sari, Yulianda (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
In running a restaurant business, it must have its own tendency to make it look different from its competitors. Rumah Makan Hasrat is recognized as a restaurant that serves Malaya specialties and has to consider different aspects in order to maintain customer satisfaction. High prices, inadequate building forms, and insufficient consumer facilities are the main issues in this study. The aim of this study is therefore to examine the aspects that affect purchase decisions and customer satisfaction at the Desire Restaurant. The study was undertaken using path analysis. There had been 100 respondents involved. The results obtained were all constructs had a significant effect on purchasing decisions and customer satisfaction. The author suggests that, in order to enhance service to customers or consumers, Rumah Makan hasrat should pay attention to the complaints and inputs submitted by customers and resolve them immediately. Â